Myocarditis in athletes after COVID-19 infection: The heart is not the only place to screen - Ibarrola, M.; Dávolos, I. (Sports Medicine and Health Science, 2020)
COVID-19 patients are susceptible to hypercoagulability. For the safe return to sports after COVID-19, athletes or individuals wanting to resume physical activity should complete screening for myocardial injury and myocarditis. In addition, patients with COVID-19 are reported at prevalence of 27% to 31% for venous thromboembolic events. The probability of deep vein thrombosis and pulmonary embolism prior to intensive exercise after COVID-19 infection should be considered. The prevalence of cardiac injury is reported at 19%, and the prevalence of deep vein thrombosis and pulmonary embolism is higher than that for myocarditis. Thus, the heart is not the only system needing screened. Examination for myocardial injury and myocarditis are mandatory. Also, deep vein thrombosis, and pulmonary thromboembolism must be considered, and when possible, blood troponin values, D-dimer prothrombin time, and activated partial thromboplastin time levels are determined for COVID-19 infection athletes or any individual before returning to sporting practice or intense physical activity or exercise.